Efficacy of intratympanic or postauricular subperiosteal corticosteroid injection combined with systemic corticosteroid in the treatment of sudden sensorineural hearing loss: A prospective randomized study - Xie, Wen; Karpeta, Niki; Liu, Jiali; Peng, Haisen; Li, Chunhua; Zhang, Zhiling; Liu, Yuehui; Duan, Maoli (Frontiers in Neurology, 2023)
Objectives This study aimed to investigate the efficacy and safety of intratympanic or postauricular subperiosteal glucocorticoid injection combined with systemic glucocorticoid in the treatment of sudden sensorineural hearing loss (SSNHL). Methods This study is a prospective randomized controlled study. This study included unilateral SSNHL patients who were hospitalized in our department between January 2020 and June 2021. Patients were randomly divided into three groups (groups A, B, and C). Patients in group A were treated with an intratympanic corticosteroid injection combined with systemic corticosteroid treatment, and patients in group B received a postauricular corticosteroid injection combined with systemic corticosteroid treatment. Patients in group C (control group) were treated with systemic corticosteroid alone. The case number of groups A, B, and C was 311, 375, and 369, respectively. Results There was no significant difference in gender distribution, the proportion of left and right affected ears, and the average interval from onset to treatment among the three groups (P > 0.05). However, there were significant differences in their average age, distribution of audiogram type, and hearing loss levels among them (P < 0.01). Our study shows that there was no significant difference in average hearing threshold improvement before and after treatment in the three groups (P > 0.05). Regarding the complications, in group A, 33 patients (10.6%) had a transient vertigo attack during tympanic injection, which lasted for ~1–3 min. In group B, 20 patients (6.43%) complained of pain at the injection site, which disappeared after 1–3 days. No other complications occurred in all the other patients. Conclusion The addition of intratympanic or postauricular corticosteroid to systemic steroids did not result in a significant effect on hearing recovery in SSNHL. No obvious complications occur in SSNHL patients treated with intratympanic injection or postauricular injection of corticosteroid. Clinical trial registration [chictr.org.cn], registration number: ChiCTR2100048762.